Pengaruh Opini Audit, Intergovernmental Revenue, dan Tax Effort terhadap Kinerja Keuangan Pemerintah Daerah Kabupaten/Kota di Provinsi Sumatera Barat Tahun 2018-2022 - Sari, Bunga Permata; Arza, Fefri Indra (Universitas Negeri Padang, 2025)
This study aims to determine the effect of audit opinion, intergovernmental revenue and tax effort on local government financial performance. The population in this study were regencies / cities in West Sumatra Province in 2018-2022 using SPSS 25 software. This study uses secondary data with a sample of 19 districts / cities for five years, taken through the total sampling method. This study uses multiple linear regression analysis to test the hypothesis. The results showed that intergovernmental revenue and tax effort have a significant positive effect on local government financial performance, while audit opinion has no significant effect on local government financial performance. It is expected that additional independent variables that affect the financial performance of local governments will be selected for future study.